Flexural Behavior of RC Continuous Beams Strengthened by Cementitious Composite Materials - Afefy, Hamdy M.; Heniegal, Ashraf M.; Baraghith, Ahmed T.; Ibrahim, Omar M. O.; Eldwiny, Mostafa E. A. (Salehan Institute of Higher Education, 2024)
Due to their great strain capacity, high tensile strength, and ability to localize cracks, cementitious composite materials are beneficial for strengthening reinforced concrete (RC) members. This paper illustrates the application of cementitious composite materials in the form of precast thin layers to strengthen a double-spanned, full-scale RC beam. Both positive and negative zones were strengthened by the precast layer embedded into the concrete cover. The precast layers have a dimension of 20 mm in thickness and 150 mm in width as that of the substrate beam and were applied by two configurations: plain and reinforced layers. A ductile smooth steel sheet with 2 mm in thickness and 100 mm in width was used inside the reinforced precast layer. The composite action of the precast layer has mutual benefits; the embedded steel sheet localizes the cracks, while the surrounding cementitious composite materials protect the steel sheet from environmental impact. The experimental results showed that the strengthening system has a significant contribution to improve the failure mode and load-carrying capacity. The use of a plain precast layer caused a 6% increase in the ultimate load and a 33% enhancement in the moment redistribution ratio compared to the control beam (CB). Applying the strengthening system with reinforced precast layer shifted the failure mode from rupture failure in the precast layer to delamination without slippage in the embedded steel sheet and matrix, leading to the full tensile capacity of the precast layer. Besides, the yielded and ultimate loads increased by 34% and 41%, respectively, and maximum deflection increased by 36%. In addition, the beam's ductility increased by 36%, and the moment redistribution ratio was enhanced by 49% compared to the CB. Doi: 10.28991/CEJ-2024-010-09-05 Full Text: PDF